Renal metastasis from papillary thyroid carcinoma: A rare case report - Huang, Wen; Hou, Zhenghui; Lin, Yuxi; Bai, Qianrong; Yuan, Menghui; Yuan, Peng (Frontiers in Oncology, 2025)
This article presents a rare case of renal metastasis from papillary thyroid carcinoma (PTC) with concurrent lung and bone metastases. Through a retrospective analysis of the patient’s diagnostic and treatment process, we aim to contribute to the development of precise treatment strategies for such rare cases, thereby improving patient prognosis.